Students’ Mathematical Reasoning Based on Polya’s Problem-Solving Stages From A Gender Perspective - Sri Utari; Dwi Rahmawati; Rahmat Bustanul Anwar; Sutrisni Andayani; Nego Sihaluhung (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to analyze the mathematical reasoning abilities of junior high school students through Polya's problem-solving stages, taking gender differences into account. A qualitative approach was employed within a descriptive research framework. Data collection was conducted at SMP Muhammadiyah 4 Metro, involving both male and female students. The data collection methods included tests, interviews, and documentation to ensure accurate recording of all activities. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing/verification. To ensure data validity, the triangulation method was applied by comparing the results of tests and interviews. The findings indicate that male students demonstrate superior mathematical reasoning skills compared to female students. Furthermore, female students tend to struggle with drawing conclusions when solving problems based on the processes they undertake.